The rise of China and its implications for the muslim world - Md. , Moniruzzaman (The Statistical, Economic and Social Research and Training Centre for Islamic Countries (SESRIC), 2013)
The contemporary economic rise of China is likely to affect the international politics and political economy in many ways. China’s growth is multidimensional ranging from economic, military, education, scientific and technological. Economically powerful china will shift the epicenter of political power from the West to the east bringing a civilizational change. To maintain its economic, military and scientific growth, china will depend much on petroleum resources of the oil-rich countries around the world. Secondly, to maintain its strategic and military influence, china will use the Shanghai Cooperation Organization as a tool in the region. Because of geographic proximity to china, and changes in international relations after the September 11, the Muslim world countries are likely to develop closer relations with china to counter balance the Western influence on them.